Application of Universal and Disciplinary Design - M.L, Sokolova (International Journal of Engineering and Technology, 2018)
The present paper deals with problems of applying universal and disciplinary design both in design of individual products and devices, and in formation of environmental elements. Recommendations are given on the use of the principles of universality and disciplinary as the main governing principles of design, as well as on the formation of competence in the use of universal and disciplinary design. When training specialists in the field of design.Â Â